A GEFI collaborative exercise on DNA/RNA co-analysis and mRNA profiling interpretation. (December 2017) - Carnevali, E.; Lacerenza, D.; Severini, S.; Alessandrini, F.; Bini, C.; Di Nunzio, C.; Di Nunzio, M.; Fabbri, M.; Fattorini, P.; Piccinini, A.; Ponzano, E.; Portera, G.; et al.
Abstract: A collaborative exercise on DNA/RNA co-analysis and RNA cell typing involving 15 GEFI (Italian working group of ISFG) laboratories was organized in collaboration with the Netherlands Forensic Institute. Participants received: 1) PCR primers for a 19-plex mRNA profiling assay, with reference purified PCR products for each cell type targeted in the multiplex; 2) detailed protocols for DNA/RNA co-extraction, mRNA profiling, and interpretation of results; 3) a set of 8 mock forensic stains (7 single source, one a mixture of two body fluids). All but one laboratory generated correct DNA typing results. As expected, stochastic effects were seen for low template DNA extracted from a skin stain. As for mRNA profiling, the percentage of laboratories that correctly identified body fluids was ≥60% for blood, saliva, vaginal mucosa, semen, and skin. Success rates were <50% for menstrual secretions, nasal mucosa, and the mixed stain (menstrual secretions and saliva).